Facial emotion recognition with AI - Ballesteros, Jesús A. (2024)
The paper presents a work with AI on using computer vision algorithms to detect human emotions in the context of the video when the user looks at different video images. This work aims to present the development of software that detects emotions by recognizing users’ facial expressions using AI algorithms and image process pipelines. The process of seeing emotions is done by evaluating users with images, which has allowed the application of computer vision algorithms that detect images according to the authors of the discipline of psychology, who propose the emotions and how they can be recognized. In this work, it has been demonstrated that it is possible to recognize emotions with the algorithms used and the development and training of the software performed from facial expressions. However, for a correct interpretation of emotions, the system must be trained in a context with more images and other complementary algorithms that allow differentiating emotions represented by facial expressions with very similar patterns to improve certainty and accuracy.